Alternate wetting and drying: a water‑saving technology for sustainable rice production in Burkina Faso? - Johnson, J.M.; Becker, M.; Kabore, J.E.; Dossou-Yovo, Elliott Ronald; Saito, Kazuki (2024)
With emerging water scarcity and rising fertilizer prices, optimising future water use while maintaining yield and nutrient efficiency in irrigated rice is crucial. Alternate wetting and moderate soil drying irrigation (i.e., re-irrigation when the water level reaches 15 cm below the soil surface) has proven to be an efficient water-saving technology in semi-arid zones of West Africa, reducing water inputs without yield penalty. Alternate wetting and severe soil drying (AWD30), by re-irrigating fields only when the water table reaches 30 cm below the soil surface, may further reduce water inputs compared to farmers’ irrigation practices (FP). However, acute soil drying may impair fertilizer use efficiency and reduce the bio-availability of some key nutrients. This study assessed the potentials and risks associated with AWD30 for smallholder rice farmers in the semi-arid zones of West Africa. We conducted 30 on-farm field trials over three seasons (wet and dry seasons of 2019, and dry season of 2020), in Kou Valley, Burkina Faso. We assessed yield, water productivity, nutrient uptake, and use efficiency under AWD30 and FP. In FP, farmers maintained their fields submerged as frequently as possible according to the scheme-dependent water provision schedule. With AWD30, irrigation frequency was reduced by 30%, however, soils were seldom completely dried due to a shallow groundwater table. Compared to FP, AWD30 reduced irrigation water input by 37% with no significant effects on grain yields (average of 4.5 Mg ha−1), thus increasing average water productivity by 39%. Both irrigation management practices provided comparable crop uptake of N, P, and K, and use efficiencies of applied N and P. However, the N content in straw and the P concentration in grain generally increased with total water input (rain + irrigation). We conclude that at locations with a shallow groundwater table, AWD30 can effectively save irrigation water without significantly reducing the grain yield and the use efficiency of applied mineral nutrients.